Brgy. elektronika promoting local independent electronic music to college students in Quezon City - Muncada, Paolo Jamin L.
Independent electronic music in the Philippines, in its present state, finds itself in a period of uncertainties and possibilities. While there is currently a growing audience for it, the struggle in legitimizing it in local music culture remains true as rock-based & traditional band music continue to dominate the independent music scene, leaving limited space for diverse musical acts. Therefore, local independent electronic artists bear the two-fold struggle of operating independently while being an artist who makes music outside of expected musical standards. With this, the research study aimed to design an intervention as a response to the question: how might we increase listenership to local independent electronic music among college students in Quezon City?